Crystal gel particle medium embedded with bacterial cellulose and preparation method of crystal gel particle medium

By inserting bacterial cellulose particles into the crystal glue particles and introducing quaternary ammonium-based functional groups for grafting modification, the existing crystal glue has poor mechanical properties and low adsorption amounts, achieving more efficient separation performance and a crystal glue particle medium that is easier to produce on a large scale.

CN119608126APending Publication Date: 2025-03-14ZHEJIANG UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510062506.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing crystal glues with embedded bacterial cellulose are mostly integrated continuous beds, which are difficult to be used on a large scale. However, the granular crystal glues that are easy to use on a large scale have poor mechanical properties and low adsorption.

Method used

By using hydroxyethyl methacrylate (HEMA) and polyethylene glycol diacrylate (PEGDA) as composite frameworks, bacterial cellulose particles are embedded to prepare crystal gel particles medium of microsphere-like porous material, and quaternary ammonium-based anion exchange functional groups are introduced on its surface for graft modification.

Benefits of technology

It improves the mechanical properties and adsorption properties of crystal glue particles, enhances their separation efficiency, and makes them more suitable for large-scale production and application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119608126A_ABST
    Figure CN119608126A_ABST
Patent Text Reader

Abstract

The invention discloses a cryogel particle medium embedded with bacterial cellulose and a preparation method of the cryogel particle medium. The embedded bacterial cellulose crystal gel medium is a porous particle, the particle size is 2-5mm, the aperture is 5-600mu m, and the porosity is 65-85%; after the cryogel particles are chemically modified, bovine serum albumin is used as model protein, so that the cryogel particles have relatively high adsorption capacity. According to the cryogel, hydroxyethyl methylacrylate and polyethylene glycol diacrylate of embedded bacterial cellulose particles serve as a framework, anion exchange functional groups are grafted, and grafting conditions are optimized. The cryogel particle separation medium has the advantages of being good in biocompatibility, excellent in permeability, high in porosity, large in protein adsorption capacity and the like, and due to the fact that the bacterial cellulose particles are embedded, the cryogel particle separation medium has more grafting sites; the preparation method provided by the invention is simple, uniform in particle size and convenient for large-scale production, and has a wide application prospect in the field of biological separation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biochemical separation, and in particular relates to a bacterial cellulose-embedded crystal gel particle medium and a preparation method thereof. Background Art

[0002] Crystal gel medium is a new type of porous material for chromatographic separation proposed in recent years. It is prepared by freezing crystallization pores and monomer polymerization and cross-linking reaction. It has ultra-large pores ranging from several microns to hundreds of microns. It has the advantages of high specific surface area, high permeability, high porosity, low mass transfer resistance, good recovery performance and high biocompatibility. It allows biological macromolecules to pass through it quickly, adsorb and desorb, and has high separation efficiency. It has broad application prospects in the field of biochemical separation. Bacterial cellulose has the advantages of strong mechanical properties, high water content, large specific surface area, and high biocompatibility. At the same time, it contains rich hydroxyl groups. Embedding it into crystal gel can improve the mechanical strength and specific surface area of ​​crystal gel, and increase its modification sites to improve adsorption performance and separation efficiency.

[0003] Existing crystal colloids embedded with bacterial cellulose are mostly whole continuous beds, which are difficult to use industrially on a large scale. Granular crystal colloids that are easy to use on a large scale have disadvantages such as poor mechanical properties and low adsorption capacity. Therefore, the crystal colloid embedded with bacterial cellulose is prepared into granules, which can improve the mechanical properties of the crystal colloid particles and increase the grafting sites. At the same time, quaternary ammonium anion exchange functional groups are introduced to modify the surface by grafting, and the grafting conditions are optimized to make it have higher adsorption performance and improve separation efficiency. At present, there are no reports on the preparation of crystal colloid granular media embedded with bacterial cellulose and the optimization of the grafting of quaternary ammonium anion exchange functional groups on the crystal colloid matrix. Summary of the invention

[0004] In view of the above problems existing in the prior art, the purpose of the present invention is to provide a crystal gel granular medium embedded with bacterial cellulose and a preparation method thereof, so as to solve the problems that the existing crystal gel embedded with bacterial cellulose is mostly an integral continuous bed, which is difficult to be used industrially on a large scale, while the granular crystal gel that is easy to use on a large scale has poor mechanical properties and low adsorption capacity.

[0005] To achieve the above object, the present invention adopts the following technical solution: A bacterial cellulose embedded crystal colloid particle medium, the crystal colloid particle medium is a microspherical porous material, which has hydroxyethyl methacrylate (HEMA) and polyethylene glycol diacrylate (PEGDA) embedded with bacterial cellulose particles as a composite skeleton, has ultra-large pores with a size of micrometers, and the crystal colloid particle medium has a quaternary ammonium anion exchange functional group.

[0006] The bacterial cellulose embedded crystal colloid particle medium has a particle size of 2-5 mm, a porosity of 65-85%, a pore size of 5-600 μm, and an adsorption capacity of 1.5-20 mg / g (wet crystal colloid) for bovine serum albumin.

[0007] The method for preparing the bacterial cellulose embedded crystal gel particle medium comprises the following steps: S1: Hydroxyethyl methacrylate (HEMA) and polyethylene glycol diacrylate (PEGDA) are dispersed in ultrapure water at a mass ratio of 75-80:25-20 to prepare a monomer solution, wherein the total mass fraction of HEMA and PEGDA in the monomer solution is 13-17%; S2: adding bacterial cellulose particles to the monomer solution in step S1, wherein the amount of bacterial cellulose particles is 13-17% of the total mass of HEMA and PEGDA, and stirring and dispersing the mixture to obtain a particle suspension; S3: adding an initiator and an accelerator to the particle suspension stirred evenly in step S2, and after continuing to stir evenly, passing the suspension through a needle with an inner diameter of 1.5-2.5 mm at a certain flow rate to form reaction suspension droplets of uniform size;

[0008] S4: dropping the suspension obtained in step S3 into an oil phase at -30 to -10°C for freeze-crystallization pore-forming and polymerization reaction, thawing at room temperature after the reaction, and removing the residual oil phase, unreacted monomers, initiators and accelerators with a large amount of ultrapure water to obtain composite crystal colloid particles;

[0009] S5: Under the action of a catalyst, a monomer with a quaternary ammonium functional group is grafted onto the composite cryogel particles obtained in step S4 through a grafting reaction to obtain a cryogel particle medium with ultra-large pores and embedded bacterial cellulose. The preparation is completed.

[0010] Furthermore, in step S3, the initiator is ammonium persulfate, and the amount used is 2.5-3.5% of the total mass of HEMA and PEGDA, preferably 3.0%; the accelerator is tetramethylethylenediamine, and the amount used is 0.5-1.5% of the total mass of HEMA and PEGDA, preferably 1.0%.

[0011] Furthermore, in step S3, the flow rate of the bacterial cellulose-containing suspension flowing into the needle is 1-3 cm / min, preferably 2 cm / min; the inner diameter of the needle used is 1.5-2.5 mm, preferably 1.9 mm.

[0012] Furthermore, in step S3, the size of the droplets of the suspension is 2-5 mm.

[0013] Furthermore, in step S5, during the grafting reaction, the composite crystal gel particles are sequentially immersed in a beaker containing a catalyst solution and a grafting monomer solution and stirred for grafting.

[0014] Further, in step S5, the catalyst is Cu 3+ Ionic solution; concentration is 0.04~0.06 M; the monomer with quaternary ammonium functional group for grafting reaction is methacryloyloxyethyl trimethyl ammonium chloride, and the concentration of grafting monomer is 0.25~3M, preferably 0.5M.

[0015] Furthermore, in step S5, the temperature for the grafting reaction is 65-90°C, preferably 80°C.

[0016] Furthermore, in step S5, the grafting reaction is carried out for 0.5 to 3 h, preferably 2 h.

[0017] In the process of preparing the crystal gel of the present invention, the water in the monomer reaction solution begins to partially freeze when the temperature is lowered, resulting in an increase in the concentration of the unfrozen monomer solution, thereby starting polymerization under the action of an initiator and an accelerator. The frozen ice acts as a porogen, causing the polymer to polymerize in the pores between the ice crystals to form a polymer skeleton. After sufficient reaction and thawing, a porous polymer crystal gel is formed.

[0018] During the polymerization reaction, hydroxyethyl methacrylate forms a free radical monomer under the action of an initiator, and copolymerizes with other free radical monomers to form a long chain. At the same time, polyethylene glycol diacrylate uses the hydroxyl groups on hydroxyethyl methacrylate to cross-link the formed long chains to finally form an overall polymer.

[0019] During the crystal gel grafting process, the catalyst solution reacts with the hydroxyl groups on the inner surface of the crystal gel to convert the hydroxyl groups into oxygen free radicals. Subsequently, the carbon-carbon double bonds on the grafted monomer react with the oxygen free radicals to connect the grafted monomer to the polymer backbone, thus completing the grafting process.

[0020] Compared with the prior art, the beneficial technical effects of the present invention are: 1. The crystal gel medium provided by the present invention is embedded with bacterial cellulose particles, which further increases the specific surface area and modification sites of the crystal gel, while improving the mechanical strength and biocompatibility of the crystal gel medium. On this basis, it is prepared into particles, which further increases its specific surface area. The inner surface is then modified with a monomer with a quaternary ammonium functional group, so that it has higher adsorption performance. The crystal gel prepared into particles is also easier to mass produce and its application range is broadened.

[0021] 2. The present invention tests the grafting effect under different conditions when performing surface modification grafting on crystal colloid particles, and selects the optimal grafting condition parameters, thereby further improving the adsorption performance and separation efficiency of the crystal colloid particle grafting.

[0022] 3. The crystal gel particle separation medium provided by the present invention has the advantages of good biocompatibility, excellent permeability, high porosity, large protein adsorption capacity, etc., and because of the embedded bacterial cellulose particles, it has more grafting sites; the preparation method provided by the present invention is simple, the particle size is uniform, and it is convenient for large-scale production, and has broad application prospects in the field of biological separation. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is an actual morphology of the bacterial cellulose embedded crystal gel particle medium of the present invention.

[0024] Figure 2 This is a pore structure diagram (SEM) of the bacterial cellulose embedded crystal gel particle medium of the present invention. DETAILED DESCRIPTION

[0025] The present invention will be further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0026] In the following examples, HEMA is hydroxyethyl methacrylate, PEGDA is polyethylene glycol diacrylate, the initiator and accelerator are ammonium persulfate and tetramethylethylenediamine, respectively, and the protein solution refers to bovine serum albumin solution. Example 1

[0027] The bacterial cellulose membrane was soaked in a 3.0 M sodium hydroxide solution and heated at 95 °C for 2 h, then rinsed with a large amount of ultrapure water to remove the sodium hydroxide, and then made into particles with a particle size of less than 500 μm and squeezed dry. HEMA and PEGDA were added to ultrapure water in a mass ratio of 77:23 to prepare a monomer solution, in which the total mass concentration of HEMA and PEGDA was 15% (w / w). The bacterial cellulose particles squeezed dry were added to the stirred monomer solution in proportion, accounting for 15% (w / w) of the total mass of the monomers (HEMA and PEGDA). After the stirred particle suspension was fully precooled in a 0 ℃ ice water bath, an initiator and an accelerator were added, wherein the initiator accounted for 3.0% (w / w) of the total mass of the monomers (HEMA and PEGDA), and the accelerator accounted for 1.0% (w / w) of the total mass of the monomers (HEMA and PEGDA). After stirring for 10 s, the reaction liquid was prepared into reaction droplets with a diameter range of 2~5 mm through a needle (inner diameter 1.9 mm) at a flow rate of 2.0 cm / s, and the droplets were dropped into white oil at a temperature of -30 ℃. The low-temperature reaction was continued for 48 h, and the crystal gel particles were taken out, thawed at room temperature, and rinsed with a large amount of ultrapure water. The crystal gel particles were subjected to grafting reaction. 0.5 g of wet crystal gel particles were weighed and immersed in the catalyst solution and stirred. After reacting for 40 min, the crystal gel particles were transferred and immersed in the monomer solution and stirred. The grafting monomer was methacryloyloxyethyltrimethylammonium chloride, the concentration of the monomer solution was 0.5 M, the amount of the monomer solution was 30 ml, the monomer reaction time was 2 h, and the grafting reaction catalyst was 0.05 M Cu 3+ ion solution, the amount of catalyst was 30 ml, and the grafting reaction temperature was 80 ℃. The porosity of the obtained composite crystal gel medium was 70%, and the pore size was 5-600 μm. 10 ml of a protein solution with a concentration of 2 mg / ml was prepared, and the grafted crystal gel particles were immersed in the protein solution for static adsorption. After 48 hours, the adsorption capacity of the composite crystal gel particle medium for protein was 15.4 mg / g (wet crystal gel). Example 2

[0028] The bacterial cellulose membrane was soaked in a 2.0 M sodium hydroxide solution and heated at 90 °C for 3 h, then rinsed with a large amount of ultrapure water to remove the sodium hydroxide, and then made into particles with a particle size of less than 500 μm and squeezed dry. HEMA and PEGDA were added to ultrapure water at a mass ratio of 77:23 to prepare a monomer solution, in which the total mass concentration of HEMA and PEGDA was 15% (w / w). The bacterial cellulose particles squeezed dry were added to the stirred monomer solution in proportion, accounting for 15% (w / w) of the total mass of the monomers (HEMA and PEGDA). After the stirred particle suspension was fully precooled in a 4 ℃ ice water bath, an initiator and an accelerator were added, wherein the initiator accounted for 2.5% (w / w) of the total mass of the monomers (HEMA and PEGDA), and the accelerator accounted for 1.0% (w / w) of the total mass of the monomers (HEMA and PEGDA). After stirring for 20 s, the reaction liquid was prepared into reaction droplets with a diameter range of 2~5 mm through a needle (inner diameter 1.9 mm) at a flow rate of 1.5 cm / s, and the droplets were dropped into white oil at a temperature of -25 ℃. The low-temperature reaction was continued for 48 h, the crystal gel particles were taken out, thawed at room temperature, and rinsed with a large amount of ultrapure water. The crystal gel particles were grafted. 0.5 g of wet crystal gel particles were weighed and immersed in the catalyst solution and stirred. After 40 min of reaction, the crystal gel particles were transferred and immersed in the monomer solution and stirred. The grafted monomer was methacryloyloxyethyl trimethylammonium chloride, the concentration of the monomer solution was 2.0 M, the amount of the monomer solution was 25 ml, the monomer reaction time was 3 h, and the grafting reaction catalyst was 0.03 M Cu 3+ ion solution, the amount of catalyst was 25 ml, and the grafting reaction temperature was 80 ℃. The porosity of the obtained composite crystal gel medium was 67%, and the pore size was 5-600 μm. 10 ml of a protein solution with a concentration of 2 mg / ml was prepared, and the grafted crystal gel particles were immersed in the protein solution for static adsorption. After 24 hours, the adsorption capacity of the composite crystal gel particle medium for protein was 13.6 mg / g (wet crystal gel). Example 3

[0029] The bacterial cellulose membrane was soaked in 2.5 M sodium hydroxide solution and heated at 80 °C for 4 h, then washed with a large amount of ultrapure water to remove the sodium hydroxide, and then made into particles with a particle size of less than 500 μm and squeezed out the water. HEMA and PEGDA were added to ultrapure water in a mass ratio of 77:23 to prepare a monomer solution, in which the total mass concentration of HEMA and PEGDA was 15% (w / w). The bacterial cellulose particles squeezed out of water were added to the stirred monomer solution in proportion, which accounted for 15% (w / w) of the total mass of the monomers (HEMA and PEGDA). After the stirred particle suspension was fully precooled in a 2 ℃ ice water bath, an initiator and an accelerator were added, wherein the initiator accounted for 2.5% (w / w) of the total mass of the monomers (HEMA and PEGDA), and the accelerator accounted for 1.5% (w / w) of the total mass of the monomers (HEMA and PEGDA). After stirring for 30 s, the reaction liquid was prepared into reaction droplets with a diameter range of 2~5 mm through a needle (inner diameter 1.9 mm) at a flow rate of 2.5 cm / s, and the droplets were dropped into white oil at a temperature of -20 ℃. The low-temperature reaction was continued for 48 h, the crystal gel particles were taken out, thawed at room temperature, and rinsed with a large amount of ultrapure water. The crystal gel particles were grafted. 0.5 g of wet crystal gel particles were weighed and immersed in the catalyst solution and stirred. After 40 min of reaction, the crystal gel particles were transferred and immersed in the monomer solution and stirred. The grafted monomer was methacryloyloxyethyl trimethylammonium chloride, the monomer solution concentration was 1.5 M, the monomer solution dosage was 35 ml, the monomer reaction time was 1.5 h, and the grafting reaction catalyst was 0.04 M Cu 3+ ion solution, the amount of catalyst was 35 ml, and the grafting reaction temperature was 85 ℃. The obtained composite crystal gel medium had a porosity of 65% and a pore size of 5-600 μm. 10 ml of a 2 mg / ml protein solution was prepared, and the grafted crystal gel particles were immersed in the protein solution for static adsorption. After 32 hours, the adsorption capacity of the composite crystal gel particle medium for protein was 8.9 mg / g (wet crystal gel). Example 4

[0030] The bacterial cellulose membrane was immersed in a 1.5 M sodium hydroxide solution and heated at 98 °C for 2 h, then rinsed with a large amount of ultrapure water to remove the sodium hydroxide, and then made into particles with a particle size of less than 500 μm and squeezed dry. HEMA and PEGDA were added to ultrapure water in a mass ratio of 77:23 to prepare a monomer solution, in which the total mass concentration of HEMA and PEGDA was 15% (w / w). The bacterial cellulose particles squeezed dry were added to the stirred monomer solution in proportion, accounting for 15% (w / w) of the total mass of the monomers (HEMA and PEGDA). After the stirred particle suspension was fully precooled in an ice water bath at 1°C, an initiator and an accelerator were added, wherein the initiator accounted for 3.5% (w / w) of the total mass of the monomers (HEMA and PEGDA), and the accelerator accounted for 0.5% (w / w) of the total mass of the monomers (HEMA and PEGDA). After stirring for 15 s, the reaction liquid was prepared into reaction droplets with a diameter range of 2~5 mm through a needle (inner diameter 1.9 mm) at a flow rate of 2.5 cm / s, and the droplets were dropped into white oil at a temperature of -25°C. The low-temperature reaction was continued for 48 h, the crystal gel particles were taken out, thawed at room temperature, and rinsed with a large amount of ultrapure water. The crystal gel particles were grafted. 3.5 g of wet crystal gel particles were weighed and immersed in the catalyst solution and stirred. After 40 min of reaction, the crystal gel particles were transferred and immersed in the monomer solution and stirred. The grafted monomer was methacryloyloxyethyl trimethylammonium chloride, the concentration of the monomer solution was 0.5 M, the amount of the monomer solution was 40 ml, the monomer reaction time was 2 h, and the grafting reaction catalyst was 0.06 M Cu 3+ ion solution, the amount of catalyst was 40 ml, and the grafting reaction temperature was 80 ℃. The obtained composite crystal gel medium had a porosity of 60% and a pore size of 5-600 μm. The grafted crystal gel particles were filled into a glass column and compressed to a filling column length of 3 cm. 50 ml of a protein solution with a concentration of 1 mg / ml was prepared as a sample solution for chromatography. The adsorption capacity of the crystal gel particle filling column for protein was 3.0 mg / mL (filling column volume) after detection. Example 5

[0031] The bacterial cellulose membrane was immersed in a 1.0 M sodium hydroxide solution and heated at 96 °C for 4.5 h, then rinsed with a large amount of ultrapure water to remove the sodium hydroxide, and then made into particles with a particle size of less than 500 μm and squeezed dry. HEMA and PEGDA were added to ultrapure water in a mass ratio of 77:23 to prepare a monomer solution, in which the total mass concentration of HEMA and PEGDA was 15% (w / w). The bacterial cellulose particles squeezed dry were added to the stirred monomer solution in proportion, accounting for 15% (w / w) of the total mass of the monomers (HEMA and PEGDA). After the stirred particle suspension was fully precooled in a 0 ℃ ice water bath, an initiator and an accelerator were added, wherein the initiator accounted for 3.5% (w / w) of the total mass of the monomers (HEMA and PEGDA), and the accelerator accounted for 1.5% (w / w) of the total mass of the monomers (HEMA and PEGDA). After stirring for 30 s, the reaction solution was prepared into reaction droplets with a diameter range of 2~5 mm through a needle (inner diameter 1.9 mm) at a flow rate of 1.0 cm / s, and the droplets were dropped into white oil at a temperature of -20 ℃. The low-temperature reaction was continued for 48 h, the crystal gel particles were taken out, thawed at room temperature, and rinsed with a large amount of ultrapure water. The crystal gel particles were grafted. 3.5 g of wet crystal gel particles were weighed and immersed in the catalyst solution and stirred. After 40 min of reaction, the crystal gel particles were transferred and immersed in the monomer solution and stirred. The grafted monomer was methacryloyloxyethyl trimethylammonium chloride, the concentration of the monomer solution was 0.5 M, the amount of the monomer solution was 36 ml, the monomer reaction time was 2 h, and the grafting reaction catalyst was 0.055 M Cu 3+ ion solution, the amount of catalyst was 36 ml, and the grafting reaction temperature was 80 ℃. The porosity of the obtained composite crystal gel medium was 63%, and the pore size was 5~600 μm. The grafted crystal gel particles were filled into a glass column and compressed to a filling column length of 5 cm. 30 ml of a protein solution with a concentration of 1 mg / ml was prepared as a sample solution for chromatography. The adsorption capacity of the crystal gel particle filling column for protein was 1.1 mg / mL (filling column volume) after detection.

[0032] like Figure 1 This is an actual morphology of the bacterial cellulose embedded crystal gel particle medium prepared in an embodiment of the present invention; it can be seen from the figure that the particle size is uniform and the size is suitable as a filling column filler. Figure 2 This is a pore structure diagram (SEM) of the crystal gel particle medium embedded with bacterial cellulose; as can be seen from the figure, there are small protruding particles on the inner surface of the particles, indicating that the bacterial cellulose is successfully embedded in the skeleton.

[0033] The contents described in this specification are merely an enumeration of implementation forms of the inventive concept, and the protection scope of the present invention should not be regarded as being limited to the specific forms described in the embodiments.

Claims

1. A bacterial cellulose embedded crystal granular medium, characterized in that The crystal colloid particle medium is a microspherical porous material with hydroxyethyl methacrylate and polyethylene glycol diacrylate embedded with bacterial cellulose particles as a composite skeleton, and has ultra-large pores in the micron range. The crystal colloid particle medium carries a quaternary ammonium anion exchange functional group; the particle size of the crystal colloid particle medium ranges from 2 to 5 mm, the porosity is 65 to 85%, the pore size is 5 to 600 μm, and the adsorption capacity for bovine serum albumin calculated based on the unit wet crystal colloid mass is 1.5 to 20 mg / g.

2. The method for preparing a bacterial cellulose embedded crystal colloid particle medium according to claim 1, characterized in that The following steps are involved: S1: Hydroxyethyl methacrylate and polyethylene glycol diacrylate are dispersed in ultrapure water at a mass ratio of 75-80: 25-20 to prepare a monomer solution, wherein the total mass fraction of hydroxyethyl methacrylate and polyethylene glycol diacrylate in the monomer solution is 13-17%; S2: adding bacterial cellulose particles to the monomer solution in step S1, wherein the amount of bacterial cellulose particles is 13-17% of the total mass of hydroxyethyl methacrylate and polyethylene glycol diacrylate, and stirring and dispersing the mixture to obtain a particle suspension; S3: adding an initiator and an accelerator to the particle suspension stirred evenly in step S2, and after continuing to stir evenly, passing the suspension through a needle with an inner diameter of 1.5-2.5 mm at a certain flow rate to form reaction suspension droplets of uniform size; S4: Dropping the suspension obtained in step S3 into an oil phase at -30 to -10°C for freeze crystallization and polymerization reaction, thawing at room temperature after the reaction, and removing the residual oil phase, unreacted monomers, initiator and accelerator with a large amount of ultrapure water to obtain composite crystal colloid particles; S5: Under the action of a catalyst, a monomer with a quaternary ammonium functional group is grafted onto the composite cryogel particles obtained in step S4 through a grafting reaction to obtain a cryogel particle medium with ultra-large pores and embedded bacterial cellulose. The preparation is completed.

3. The method for preparing a bacterial cellulose embedded crystal colloid particle medium as claimed in claim 2, characterized in that In step S3, the initiator is ammonium persulfate, and the amount used is 2.5-3.5% of the total mass of hydroxyethyl methacrylate and polyethylene glycol diacrylate, preferably 3.0%; the accelerator is tetramethylethylenediamine, and the amount used is 0.5-1.5% of the total mass of hydroxyethyl methacrylate and polyethylene glycol diacrylate, preferably 1.0%.

4. The method for preparing a bacterial cellulose embedded crystal colloid particle medium according to claim 2, characterized in that In step S3, the flow rate of the suspension containing bacterial cellulose flowing into the needle is 1-3 cm / min, preferably 2 cm / min; the inner diameter of the needle used is 1.5-2.5 mm, preferably 1.9 mm.

5. The method for preparing a bacterial cellulose embedded crystal colloid particle medium as claimed in claim 2, characterized in that In step S3, the size of the suspension droplets is 2-5 mm.

6. The method for preparing a bacterial cellulose embedded crystal colloid particle medium as claimed in claim 2, characterized in that In step S5, the catalyst is Cu 3+ Ionic solution; concentration is 0.04~0.06 M; during the grafting reaction, the composite crystal gel particles are immersed in a beaker containing a catalyst solution and a grafting monomer solution in turn and stirred for grafting.

7. The method for preparing a bacterial cellulose embedded crystal colloid particle medium as claimed in claim 2, characterized in that In step S5, the monomer with a quaternary ammonium functional group for the grafting reaction is methacryloyloxyethyl trimethyl ammonium chloride, and the concentration of the grafting monomer is 0.25-3 M, preferably 0.5 M.

8. The method for preparing a bacterial cellulose embedded crystal colloidal particle medium as claimed in claim 2, characterized in that In step S5, the temperature for the grafting reaction is 65-90°C, preferably 80°C.

9. The method for preparing a bacterial cellulose embedded crystal colloidal particle medium according to claim 2, characterized in that In step S5, the grafting reaction is carried out for 0.5 to 3 h, preferably 2 h.

Citation Information

Patent Citations

  • Composite continuous bed cryogel and preparation thereof, and application in separating IgG and albumin

    CN103230784A

  • Glucosan-based cryogel microsphere separating medium and preparation method thereof

    CN106632860A

  • Integral crystal gel medium embedded with bacterial cellulose and preparation method of integral crystal gel medium

    CN116102694A